Proposals for 2nd Five Year Plan Health Department (Ayurved) Vol III Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
Opening of 205 Ayurvedic dispensaries Brief description - By the end of the First Five Year Plan, there will be in all 337 Ayurvedic dispensaries in the State. It is proposed to cover the whole area of the State with Ayurvedic dispensaries situated at 5 files radius. The dispensaries will be located preferably at a place where hat or big fair is held. On the basis of this principle we shall have located about 600 Ayurveda dispensaries in all by the end of the 2nd five year plan.
Government of Madhya Bharat
Government of Madhya Bharat
Keywords: Ayurvedic Dispensaries; Ayurvedic College Hospital; Ayurvedic College; Hostel Hospital and Staff Quarters; Upgrading of Ayurvedic dispensaries; Appointment of Ayurvedic dispensaries; Ayurvedic pharmacy